Incidence of Oral Mucosal Lesions in Patients Visiting A Private Dental Institution - RAHMAN, FAHMIDA BINTI ABD; NARAYAN, VIVEK; MAHESHWARI, UMA (The journal of contemporary issues in business and government, 2021)
Oral mucosal lesions act as a protective barrier against various harmful external agents. A wide variety of lesions and conditions either harmless or with serious complications may attack oral mucosa. Therefore, proper identification and treatment of these lesions play an important role in total oral health. It is a retrospective study. A total of 41439 patient records between January 2019 and December 2019 were evaluated in this study. Data such as age, gender, types of oral mucosal lesions were retrieved from the patient records of the private dental institution, Chennai. The data are then tabulated in Microsoft Excel and subsequently transferred to SPSS software for statistical analysis. Chi square test was done and the association between age and gender with types of oral mucosal lesions were found to be statistically significant. The incidence of oral mucosal lesions was 3.79 per 1000 per year. Overall, leukoplakia (27%) had the maximum predilection followed by smoker’s palate (23%). Patients in the age group of 41 to 50 years were having the highest predilection for oral mucosal lesions (27.7%). Out of the 5 categories of oral mucosal lesions, potentially malignant disorders (60%) were highly prevalent in our study. This can be attributed to the increase in various adverse habits such as smoking, chewing tobacco, tobacco products and many more. More awareness about tobacco and its harmful effects must be promoted in order to prevent the rising numbers in potentially malignant disorders and oral cancer.